2012
DOI: 10.1007/jhep01(2012)047
|View full text |Cite
|
Sign up to set email alerts
|

D0 − $ {\overline {\text{D}}^0} $ mixing in gauge-Higgs unification

Abstract: We discuss flavor mixing and resulting Flavor Changing Neutral Current (FCNC) in the SU (3) ⊗ SU (3) color gauge-Higgs unification. As the FCNC process we calculate the rate of D 0 −D 0 mixing due to the exchange of non-zero Kaluza-Klein gluons at the tree level. Flavor mixing is argued to be realized by the fact that the bulk mass term and brane localized mass term is not diagonalized simultaneously unless bulk masses are degenerate.It is shown that automatic suppression mechanism is operative for the FCNC pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…With these parameters fixed, wave functions of quarks and leptons are determined. In the present paper, we mostly ignore the flavor mixing in the quark and lepton gauge couplings [14,[82][83][84][85][86][87][88]. It has been shown that the Cabibbo-Kobayashi-Maskawa (CKM) mixing matrix can be incorporated in GHU with naturally suppressed FCNCs (flavor changing neutral currents) [14].…”
Section: A Parameter Setsmentioning
confidence: 99%
“…With these parameters fixed, wave functions of quarks and leptons are determined. In the present paper, we mostly ignore the flavor mixing in the quark and lepton gauge couplings [14,[82][83][84][85][86][87][88]. It has been shown that the Cabibbo-Kobayashi-Maskawa (CKM) mixing matrix can be incorporated in GHU with naturally suppressed FCNCs (flavor changing neutral currents) [14].…”
Section: A Parameter Setsmentioning
confidence: 99%
“…∆F = 2 processes provide some of the most stringent constraints on NP generalizations of the SM. Several phenomenological analyses of ∆F = 2 processes have been performed in the last years, both for specific models and in model-independent frameworks [29,30,31,32,33,34,35,36,37,38,39]. A generalization of the Unitarity Triangle (UT) analysis, which allows for NP effects by including the most significant flavor constraints on NP available at the time was performed in Ref.…”
Section: Model-independent Constraints On ∆B = Operators and Np Scalementioning
confidence: 99%
“…[110]. Also, a mixing matrix in the quark sector, the Cabibbo-Kobayashi-Maskawa (CKM) mixing matrix [111,112], is introduced by brane interaction terms [77,[113][114][115][116]. We will leave further discussions for future studies.…”
Section: Summary and Discussionmentioning
confidence: 99%